Dukungan Sosial untuk Mendukung Keberhasilan Pemberian ASI Eksklusif pada Ibu Bekerja Sebagai Upaya Pencegahan Stunting di Indonesia - Rufaida Adya Nur Avianti Ulya (Universitas Airlangga, 2023)
Background: The current stunting prevalence rate in Indonesia is below the target of the National Medium Term Development Plan (RPJMN) 2020-2024, in which accounted 21.1% in 2021 and 14% in 2024. One of the efforts to eradicate stunting is exclusive breastfeeding. On the other hand, working mothers are more prone to fail to provide exclusive breastfeeding, as a result, the risk of stunting in infants with working mothers is higher. Thus, to promote exclusive breastfeeding for working mothers is social support Objectives: To review various literatures in the form of journal articles that discuss social support and the success of exclusive breastfeeding for working mothers in Indonesia. Methods: This research method was qualitative analysis by doing a literature review derived from published research articles. Articles acquired through Google Scholar database, Neliti, Pubmed and Science Direct. Article searches are using variations and combinations of the following Indonesian words